Buddhist studies - Scherrer-Schaub, Cristina .; Gombrich, Richard (Delhi : Motilal banarsidass Publishers, 2008)
This book is based on Buddha. The first three chapters of this book are autobiographical. The first chapter covers his service period (1945-1986) as government officers as well as Buddhist activist and scholar. In the second chapter are listed all his writings after retirement. His other Buddhist activities during the same period are given in the third chapter. The last three chapter sum up what others say about his innovative ideas and original research works by the way of reviews of his books, through personal letters and through awards and honours.
Includes references and index.
Keywords: Buddhist literature -- History and criticism -- Congresses. -- India; Buddhist philosophy -- -- Congresses; Buddhism -- Congresses. -- India